Dynamical Analysis of an Eco-epidemic System with Different Forms of Prey Refuges and Predator Harvesting - Islam, Md Sarijul; Hossain, Sajjad; Sarwardi, Sahabuddin (Discontinuity, Nonlinearity, and Complexity, 2026)
The present article deals with an eco-epidemiological model consisting of one prey and two predator population subjected to predator infection and predator harvesting. It has been considered two different types of functional response incorporating linear type refuge for susceptible predator and non-linear type refuge for infected predator. After formulating the model system, the positivity and boundedness of the solution, the persistence of the proposed system have been discussed. Along with the existence and stability of the biologically feasible equilibrium points, different types of bifurcation have been thoroughly investigated and in this regard, some suitable graphical representations are executed. Some numerical results are performed to support our analytical findings.